Use of a Risk Assessment Model for Venous Thromboembolism Is Associated with Decreased Prophylaxis - Gunaratne, Tarini; Schulte, Rebecca; Moss, Stephanie; Lisheba, Oleg; Rothberg, Michael B. (Journal of general internal medicine : JGIM, 2025)
Venous thromboembolism (VTE) prophylaxis is often overprescribed to patients at low risk for VTE. Whether risk assessment models (RAMs) reduce prescribing to low-risk patients is unknown. We incorporated a validated RAM into admission order sets to help physicians determine risk of VTE. To quantify RAM use, determine its association with prophylaxis, and identify patient factors associated with concordance between calculated VTE risk and prophylaxis use. We hypothesized that use of the RAM would be associated with less prophylaxis. Cross-sectional study. We excluded surgical, COVID, and intensive care unit patients, and patients with contraindication to prophylaxis or already on anticoagulation. Medical inpatients aged ≥18 years admitted to 10 US hospitals from December 2020 to March 2023. Physician RAM use. Physician prophylaxis prescription and patient characteristics. Among 131,441 patient encounters, RAM use varied across hospitals from 54 to 99%. Overall, physician ordering was concordant with the RAM's recommendation for 68% of patients. Prophylaxis prescription was less common when the RAM was used than when it was not (44% vs. 73%, p < 0.001). When calculated risk was high (i.e., >0.75%), 96% of patients had prophylaxis prescribed versus 37% when risk was low. Across hospitals, prophylaxis prescription rates varied more for low-risk (21 to 77%) than for high-risk patients (87 to 98%). Among low-risk patients, prophylaxis was associated with male sex, older age, reduced mobility, and history of DVT, stroke, heart or respiratory failure, or active cancer. Use of the RAM was associated with reduced prophylaxis prescribing, but many low-risk patients still received prophylaxis, especially if they had a risk factor for VTE. Physicians appear to agree with high-risk assessments but are less comfortable not prescribing prophylaxis to patients at low risk.